2004
DOI: 10.1093/aob/mch071
|View full text |Cite
|
Sign up to set email alerts
|

A Post-genomic Approach to Understanding Sphingolipid Metabolism in Arabidopsis thaliana

Abstract: Arabidopsis provides an excellent genetic and post-genomic model for the characterization of the roles of sphingolipids in higher plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
102
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(104 citation statements)
references
References 117 publications
(135 reference statements)
0
102
0
2
Order By: Relevance
“…This might account for the cell death phenotype in a number of cases [16-19, 45, 46]. Ceramide synthase was proposed to be a multisubunit complex, of which members of the yeast longevity assurance gene (LAG1) family, including the tomato ASC1 gene [47], are the only components identified thus far [12,48]. Whereas the dominant ASC1 allele confers FB 1 -and AAL toxin-resistance to tomato [15,49], overexpression of the mammalian LAG1 homologs UOG1 [50], TRH1 and TRH4 [51] renders 293T cells resistant to FB 1 .…”
Section: Discussionmentioning
confidence: 99%
“…This might account for the cell death phenotype in a number of cases [16-19, 45, 46]. Ceramide synthase was proposed to be a multisubunit complex, of which members of the yeast longevity assurance gene (LAG1) family, including the tomato ASC1 gene [47], are the only components identified thus far [12,48]. Whereas the dominant ASC1 allele confers FB 1 -and AAL toxin-resistance to tomato [15,49], overexpression of the mammalian LAG1 homologs UOG1 [50], TRH1 and TRH4 [51] renders 293T cells resistant to FB 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The condensing enzyme, or β-ketoacylCoA synthase (KCS), catalyzes the first of the four reactions and is both rate-limiting and specific for the chain length of acyl-CoA synthesized (Millar and Kunst, 1997). Two highly divergent families of KCSs have been identified in Arabidopsis: an FAE1-type family homologous to the first condensing enzyme demonstrated to be involved in seed oil biosynthesis (Kunst et al, 1992;James et al, 1995), and ELOs, which have homology to the Saccharomyces cerevisiae ELO family that is responsible for sphingolipid synthesis (Dunn et al, 2004). Of the 21 FAE1-type KCS enzymes in Arabidopsis , 11 have been shown by microarray analysis to be upregulated in the stem epidermis (Suh et al, 2005).…”
Section: The Biosynthesis Of Vlcfasmentioning
confidence: 99%
“…The Arabidopsis CER10 protein shows significant homology with yeast enoyl-CoA reductase Tsc13p, because it rescues the temperature-sensitive lethality of the tsc13-1 yeast mutant (12) and is involved in VLCFA synthesis (13). The Arabidopsis genome also contains a gene that shares significant homology with the yeast 3-ketoreductase YBR159w, and although it has been demonstrated that this Arabidopsis activity can rescue biochemical phenotypes of the ybr159⌬ mutant, the in vivo role of the plant gene remains to be determined (14). The yeast dehydratase PHS1/YJL097w gene also shares significant similarity with the Arabidopsis PASTICCINO2 (PAS2) gene, which was shown to rescue phs1⌬ lethality (15).…”
mentioning
confidence: 99%